IMPLEMENTASI KEWIRAUSAHAAN PENDIDIKAN DALAM MENINGKATKAN KEMANDIRIAN FINANSIAL DI SMK AL FARUQI KUBANG RAYA RIAU - Mardiah Mardiah; Ahmad Ansori; Miftahhul Rahmi; Mutiara Hikma; Mhd Renaldi Sihombing (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of educational entrepreneurship in improving financial independence at SMK Al Faruqi Kampar. This research employs a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. Observation was conducted to directly examine entrepreneurial activities, interviews were carried out with teachers and relevant stakeholders, and documentation was used to support the collected data. Data analysis was performed through data reduction, data display, and conclusion drawing. The results indicate that the implementation of educational entrepreneurship has been integrated into the learning process through production units such as bakery, café, and fashion businesses. These activities actively involve students and are managed in a structured manner, with capital sourced from practical funds, foundation support, and external assistance in the form of facilities. This entrepreneurial activity contributes to institutional income and supports financial independence. However, challenges remain, particularly time constraints due to conflicts between academic and business activities, indicating the need for more effective management to ensure sustainability.